Analisis Strategi Pemasaran Charter Kapal Anchor Handling Tug Supply (AHTS) pada Perusahaan Offshore Support Vessel - Delta Romadhona Pangesti; Trisnowati Rahayu; Ardhiana Puspitacandri; Romanda Annas Amrullah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
In Indonesia's oil and gas industry, the procurement of goods and services, including ship chartering, plays an important role in supporting the smooth operation of upstream oil and gas activities. The ever-changing dynamics of competition have a significant impact on the strategies that companies choose to implement. Additionally, companies handle various projects with varying lease durations, indicating market dynamics that demand flexible and effective strategies, especially in the competitive shipping industry. The primary objective of this study is to identify the marketing strategies implemented, identify the challenges faced in their implementation, and analyze the impact of these strategies on the sustainability of the company's business. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques were carried out through direct observation, structured interviews with marketing management, and documentation. The results of the study show that the marketing strategies used by offshore support vessel companies include Word of Mouth (WoM) and tender and direct charter systems. However, there are several challenges in their implementation, such as price fluctuations or discrepancies, as well as mismatches between the offered price and the reference price set by SKK Migas. Therefore, it is necessary to maintain or improve service quality, innovate vessel designs, or offer flexible charter packages, conduct regular evaluations to analyze market prices to avoid errors, and ensure the offshore support vessel company remains competitive and sustainable in the market.